THE IMPROVEMENT OF THE UNDERSTANDING OF THE STRUGGLE IN MAINTAINING INDONESIA’S INDEPENDENCE CONCEPT THROUGH EVERYONE IS A TEACHER HERE LEARNING MODEL SUPPORTED BY AUDIO VISUAL MEDIA - Citra Aulia Saputri; Siti Wahyuningsih; Sadiman Sadiman (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve the understanding of the struggle in maintaining Indonesia’s independence concept through the implementation of Everyone Is A Teacher Here learning model supported by audio visual media on fifth grade students of an elementary school in Surakarta.This research is a Classroom Action Research. The data obtained by doing interview, observation, test, and documentation. The validity of the data is tested using content validity and triangulation. The data analysis used is interactive analysis model.The result of this research is classical completeness on pre-action is 13, 79%, on cycle I the classical completeness increases to 53, 57%, and on cycle II the classical completeness increases to 88,89%. Based on the results of research, it is found that the implementation of Everyone Is A Teacher Here learning model supported by audio visual media improves the understanding of the struggle in maintaining Indonesia’s independence concept on on fifth grade students of an elementary school in Surakarta.